2002
DOI: 10.1590/s0103-90162002000300017
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzymatic variability of cassava accessions from different regions in Brazil

Abstract: Cassava (Manihot esculenta Crantz) belongs to the Euphorbiaceae family, and is widely cultivated in Brazil. The objective of this study was to evaluate the isoenzymatic variability of 200 cassava accessions from the germplasm bank of Embrapa Amazonia Oriental. Seven groups were formed according to their origin: 1-Amazonas, 2-Amapa, 3-Bahia, 4-Para, 5-Rondonia, 6-Various, for accessions with a maximum of three individuals per place of origin, and 7 -Accessions of indefinite origin. The accessions were also eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
3
3
0
1
Order By: Relevance
“…A similar result (64.4% variation within households) was obtained by Veasey et al (2007) when studying morphological traits of the same accessions. This same pattern of a greater portion of variation being due to differences between accessions within households has also been reported for cassava (Sambatti et al, 2000), as well as within groups or regions (Faraldo et al, 2000;Cabral et al, 2002). Other studies with sweet potatoes using AMOVA have also shown higher diversity within rather than between regions, which could, on a much smaller scale, be compared to the higher diversity found within rather than between households and communities.…”
Section: Genetic Structure and Analysis Of Molecular Variancesupporting
confidence: 74%
“…A similar result (64.4% variation within households) was obtained by Veasey et al (2007) when studying morphological traits of the same accessions. This same pattern of a greater portion of variation being due to differences between accessions within households has also been reported for cassava (Sambatti et al, 2000), as well as within groups or regions (Faraldo et al, 2000;Cabral et al, 2002). Other studies with sweet potatoes using AMOVA have also shown higher diversity within rather than between regions, which could, on a much smaller scale, be compared to the higher diversity found within rather than between households and communities.…”
Section: Genetic Structure and Analysis Of Molecular Variancesupporting
confidence: 74%
“…This result was also shown within cassava populations in Costa Rica (Zaldivar et al 2004) and Africa (Raji et al 2009), within regions or cluster groups of cassava (Mühlen et al 2000;Cabral et al 2002;Lokko et al 2006;Siqueira et al 2009), as well as within households with sweet potato (Veasey et al 2008). Peroni et al (2007) obtained values indicating that despite the higher diversity of the sweet varieties of cassava, in comparison with the bitter ones, the divergence among the two groups was low, however, significant, with most genetic diversity concentrated within groups.…”
Section: Genetic Structuresupporting
confidence: 52%
“…In order to understand the important role of traditional farmers in maintaining and even amplifying genetic diversity in cassava landraces in Brazil and other countries, various studies have been undertaken with isozyme markers ( Sambatti et al , 2000 ; Faraldo et al , 2000 ; Cabral et al , 2002 ; Resende et al , 2004 ), randomly amplified polymorphic DNA (RAPD) markers ( Colombo et al , 1998 ; Carvalho and Schaal, 2001 ; Zacarias et al , 2004 ), and microsatellites or simple sequence repeats (SSR) ( Mühlen et al , 2000 ; Carvalho and Schaal, 2001 ; Peroni, 2007 ), the latter being an appropriate marker for the detection of genetic polymorphisms, widely used to characterize genetic diversity in traditional crops ( Mühlen et al , 2000 ; Fregene et al , 2003 ; Elias et al , 2004 ; Veasey et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%